2016
DOI: 10.1186/s13071-016-1901-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ixodes ricinus blood meals using an automated protocol with high resolution melting analysis (HRMA) reveals the importance of domestic dogs as larval tick hosts in Italian alpine forests

Abstract: BackgroundIn Europe, Ixodes ricinus L. is the main vector of a variety of zoonotic pathogens, acquired through blood meals taken once per stage from a vertebrate host. Defining the main tick hosts in a given area is important for planning public health interventions; however, until recently, no robust molecular methods existed for blood meal identification from questing ticks. Here we improved the time- and cost-effectiveness of an HRMA protocol for blood meal analysis and used it to identify blood meal source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Similar results were reported for questing nymphal I. ricinus (Moran Cadenas et al. 2007 ; Collini et al 2015 , 2016 ) and questing nymphal Amblyomma americanum (Allan et al. 2010 ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Similar results were reported for questing nymphal I. ricinus (Moran Cadenas et al. 2007 ; Collini et al 2015 , 2016 ) and questing nymphal Amblyomma americanum (Allan et al. 2010 ).…”
Section: Discussionsupporting
confidence: 80%
“… 2006 ; Wodecka, Rymaszewska and Skotarczak 2013 ; Collini et al. 2016 ) but higher than in studies using the same method of analysis (49%, 43% and 39% as reported in Humair et al. 2007 ; Moran Cadenas et al.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although it seems very unlikely that only the immediate area around a dead or dying infected monkeys supports high density of KFDV-infected partially fed ticks or fully-fed larvae (which would then feed again as nymphs after moulting) that may pass infection to humans, this should be con rmed empirically. Priority should be given to quantifying the tick burden on dead and dying monkeys, assessing the number, species, stage and KFDV infection rate of these attached ticks, as well as determining the number, KFDV infection rate and blood meal identity [73] of ticks sampled from the habitat or off people near the monkey death site. (Priority 10, Table 2).…”
Section: Measures To Reduce Density and Distribution Of Infected Ticksmentioning
confidence: 99%